Method for manufacturing wavelength conversion sheet, phosphor protective film, wavelength conversion sheet with release film, and wavelength conversion sheet

By using the bonding method between the laminated film and the release film in the manufacturing process of the phosphor protective film, the problems of uneven thickness and wrinkle of the phosphor layer are solved, and the thinning and uniform luminescence effect of the wavelength conversion sheet is achieved.

CN112912772BActive Publication Date: 2025-02-18TOPPAN HOLDINGS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980070184.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-26
Filing Date
2019-10-24
Publication Date
2025-02-18
Estimated Expiration
2039-10-24

AI Technical Summary

Technical Problem

The existing fluorescent protective film is prone to wrinkles during the manufacturing process, resulting in uneven thickness of the phosphor layer, affecting the luminescent effect. As the equipment becomes thinner, it is difficult to ensure the thickness of the support film of the protective film, which further intensifies. Wrinkle problem.

Method used

A phosphor protective film is formed by bonding a laminated film with a barrier film to a release film, and a release film is provided in the phosphor layer forming step to suppress the generation of wrinkles on the protective film. The release film is peeled off during the manufacturing process and does not remain on the wavelength conversion sheet, thereby ensuring uniform thickness.

Benefits of technology

Through this method, the generation of wrinkles on the phosphor protective film can be effectively suppressed, the thickness of the phosphor layer is uniform, the luminescence effect is improved, and the filmization of the wavelength conversion sheet can be achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112912772B_ABST
    Figure CN112912772B_ABST
Patent Text Reader

Abstract

A method for manufacturing a wavelength conversion sheet comprises: a laminating step of laminating a laminate film having a barrier film and a peeling film that can be peeled off from the laminate film to obtain a phosphor protective film; a phosphor layer forming step of forming a phosphor layer containing a phosphor on a surface of one side of the laminate film of the phosphor protective film to obtain a wavelength conversion sheet with a peeling film; and a peeling step of peeling the peeling film from the wavelength conversion sheet with the peeling film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing a wavelength conversion sheet, a phosphor protective film, a wavelength conversion sheet with a release film, and a wavelength conversion sheet Background Art

[0002] In the light-emitting units such as the backlight unit and the electroluminescent light-emitting unit of the liquid crystal display, the laser light generated by the LED is sometimes incident on the phosphor to change the wavelength of the laser light. Since the color of light changes according to the change of wavelength, it is possible to display a color image by using light of various wavelengths (i.e., various colors) as display light.

[0003] However, the performance of the phosphor may be degraded due to contact with oxygen or water vapor for a long time. In order to prevent such performance degradation, a protective film is stacked on a phosphor layer containing the phosphor or the phosphor layer is sandwiched by the protective film to form a wavelength conversion sheet. Such a protective film is known, in which (for example) an inorganic thin film layer is vacuum-deposited onto a resin film, and the inorganic thin film layer blocks the penetration of oxygen and water vapor (see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-13567 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, the above-mentioned phosphor protective film may be wrinkled mainly due to the heat and tension applied to the resin film during its manufacturing process. If the phosphor layer is laminated on the protective film that has wrinkles as described above, it is difficult to form a phosphor layer with a very uniform thickness. Therefore, the resulting wavelength conversion sheet is prone to unfavorable conditions such as uneven light emission of the phosphor. As a method for suppressing the generation of the above-mentioned wrinkles, a method of increasing the thickness of the support film constituting the protective film can be cited.

[0009] On the other hand, as mobile devices such as smartphones and monitors become thinner, the wavelength conversion sheets used in these devices also need to be thinner. As the thickness of the wavelength conversion sheet further advances, the protective film needs to be thinner, and the thickness of the support film cannot be fully ensured, which makes it easier to generate wrinkles on the phosphor protective film, and the uneven light emission of the phosphor may become more obvious.

[0010] The present disclosure is completed in view of the problems of the above-mentioned prior art, and its purpose is to provide a method for manufacturing a wavelength conversion sheet, a phosphor protective film, a wavelength conversion sheet with a peeling film, and a wavelength conversion sheet, which can realize the thinning of the wavelength conversion sheet and can also suppress the generation of wrinkles on the phosphor protective film, thereby suppressing the uneven light emission of the phosphor caused by the wrinkles.

[0011] Means used to solve problems

[0012] In order to achieve the above-mentioned purpose, the present disclosure provides a method for manufacturing a wavelength conversion sheet, comprising: a laminating step of laminating a laminate film having a barrier film and a peeling film that can be peeled off from the above-mentioned laminate film to obtain a phosphor protective film; a phosphor layer forming step of forming a phosphor layer containing a phosphor on a surface of one side of the above-mentioned laminate film of the above-mentioned phosphor protective film to obtain a wavelength conversion sheet with a peeling film; and a peeling step of peeling the above-mentioned peeling film from the above-mentioned wavelength conversion sheet with the peeling film.

[0013] According to the manufacturing method, a release film is provided on the phosphor protective film until the phosphor layer forming step, and thus, the presence of the release film can sufficiently suppress the generation of wrinkles on the phosphor protective film. The release film is peeled off in the peeling step and does not remain on the obtained wavelength conversion sheet, so that a thickness sufficient to improve wrinkles can be ensured. In addition, the wavelength conversion sheet obtained through the peeling step can be sufficiently thinned.

[0014] In the manufacturing method, in the laminating step, the laminated film and the release film may be laminated with wrinkles of the laminated film smoothed out. This can more effectively suppress the generation of wrinkles on the phosphor protective film.

[0015] In the manufacturing method, in the phosphor layer forming step, the phosphor layer may be formed between two phosphor protection films, thereby more fully protecting the phosphor layer from oxygen, water vapor, etc., and more fully suppressing degradation of performance.

[0016] In the manufacturing method, the laminated film may include a support film disposed between the barrier film and the release film, and the total thickness of the support film and the release film may account for more than 60% of the total thickness of the phosphor protective film. The support film has a function of improving wrinkles together with the release film. In addition, by the total thickness of the support film and the release film accounting for more than 60% of the total thickness of the phosphor protective film, wrinkles on the phosphor protective film can be more effectively suppressed.

[0017] In the manufacturing method, the laminated film may not have a support film between the barrier film and the release film, and the thickness of the release film may account for more than 50% of the total thickness of the phosphor protective film. In this case, the wavelength conversion sheet can be made thinner by not having a support film. In addition, the thickness of the release film accounts for more than 50% of the total thickness of the phosphor protective film, thereby more effectively suppressing the formation of wrinkles on the phosphor protective film.

[0018] In the above manufacturing method, the barrier film may include a barrier film substrate, and the barrier film substrate may have a thickness of 9 μm to 25 μm.

[0019] In the above production method, the barrier film may include a barrier film substrate and an inorganic thin film layer provided on the barrier film substrate.

[0020] In the above-mentioned manufacturing method, the above-mentioned laminated film may have a functional layer on the surface of one side of the above-mentioned peeling film, and the above-mentioned functional layer may be a layer that performs at least one function selected from the group consisting of preventing interference fringes, anti-reflection function, light scattering function, antistatic function and anti-damage function.

[0021] In the manufacturing method, the deviation (3σ) of the total thickness of the laminated film may be 1.5 μm or more, and the coefficient of dynamic friction of the surface of the functional layer may be 0.4 or less. By setting the deviation (3σ) of the total thickness of the laminated film including the functional layer to 1.5 μm or more and the coefficient of dynamic friction of the surface of the functional layer to 0.4 or less, it is possible to prevent damage to the light guide plate in contact with the wavelength conversion sheet when the wavelength conversion sheet is assembled into a display.

[0022] In the above-mentioned manufacturing method, the deviation (3σ) of the total thickness of the above-mentioned phosphor protective film can be less than 1.0μm. According to the manufacturing method of this embodiment, even if the laminated film has a functional layer, by attaching a release film to the surface of the functional layer, the deviation (3σ) of the total thickness of the phosphor protective film can be reduced to less than 1.0μm. In addition, by setting the deviation (3σ) of the total thickness of the phosphor protective film to less than 1.0μm, the deviation of the thickness of the phosphor layer can be reduced when making a wavelength conversion sheet. As a result, the change in color caused by the deviation of the thickness of the phosphor layer can be suppressed, and a uniform color can be obtained.

[0023] In the manufacturing method, the peel strength between the laminate film and the release film according to JIS K6854-3 may be 0.05 N / 25 mm to 1.0 N / 25 mm. When the peel strength is within the above range, the presence of the release film can more effectively suppress the generation of wrinkles on the phosphor protection film, and the release film can be smoothly peeled off from the laminate film in the peeling step.

[0024] In addition, the present disclosure also provides a method for manufacturing a wavelength conversion sheet, comprising: a laminating step of laminating a main body portion including a support film and a peeling film that can be peeled off from the above-mentioned main body portion to obtain a phosphor protective film; a phosphor layer forming step of forming a phosphor layer including a phosphor on a surface of one side of the above-mentioned main body portion of the above-mentioned phosphor protective film to obtain a wavelength conversion sheet with a peeling film; and a peeling step of peeling the above-mentioned peeling film from the above-mentioned wavelength conversion sheet with the peeling film, the thickness of the above-mentioned peeling film accounting for more than 50% of the total thickness of the above-mentioned phosphor protective film.

[0025] According to the above-mentioned manufacturing method, a release film is provided on the phosphor protective film until the phosphor layer forming step, and thus, the existence of the release film can sufficiently suppress the generation of wrinkles on the phosphor protective film. The release film is peeled off in the peeling step and does not remain in the obtained wavelength conversion sheet, so that it can be ensured that the thickness is sufficient to improve the wrinkles. In particular, the thickness of the release film is 50% or more of the total thickness of the phosphor protective film, so that the effect of suppressing the generation of wrinkles on the phosphor protective film can be fully obtained. In addition, the wavelength conversion sheet obtained through the peeling step can be sufficiently thinned.

[0026] In the manufacturing method, in the laminating step, the main body and the release film may be laminated with wrinkles on the main body smoothed out. This can more effectively suppress the generation of wrinkles on the phosphor protection film.

[0027] In the manufacturing method, in the phosphor layer forming step, the phosphor layer may be formed between two phosphor protection films, thereby more fully protecting the phosphor layer from oxygen, water vapor, etc., and more fully suppressing degradation of performance.

[0028] In the above production method, the support film may have a thickness of 12 μm to 50 μm. Thus, a wavelength conversion sheet having sufficient strength and being sufficiently thinned can be obtained.

[0029] In the manufacturing method, the release film may have a thickness of 25 μm to 150 μm. This can prevent the total thickness of the phosphor protection film from becoming too thick and can sufficiently prevent wrinkles from being generated on the phosphor protection film.

[0030] In the above-mentioned manufacturing method, the above-mentioned laminated film may have a functional layer on the surface of one side of the above-mentioned peeling film, and the above-mentioned functional layer may be a layer that performs at least one function selected from the group consisting of preventing interference fringes, anti-reflection function, light scattering function, antistatic function and anti-damage function.

[0031] In addition, the present disclosure provides a phosphor protective film, which comprises: a laminated film having a barrier film, and a peeling film that can be peeled off from the laminated film and is provided on one surface of the laminated body. According to the phosphor protective film, by having a peelable peeling film, the generation of wrinkles on the phosphor protective film can be sufficiently suppressed. The peeling film is peeled off when manufacturing the wavelength conversion sheet and does not remain in the obtained wavelength conversion sheet, so that it can ensure a thickness sufficient to improve wrinkles. In addition, the wavelength conversion sheet obtained using the phosphor protective film can be sufficiently thinned.

[0032] In the phosphor protection film, the laminated film may include a support film disposed between the barrier film and the release film, and the total thickness of the support film and the release film may account for 60% or more of the total thickness of the phosphor protection film.

[0033] In the phosphor protection film, the laminated film may not have a support film between the barrier film and the release film, and the thickness of the release film may account for more than 50% of the total thickness of the phosphor protection film.

[0034] In the phosphor protection film, the barrier film may include a barrier film substrate, and the barrier film substrate may have a thickness of 9 μm to 25 μm.

[0035] In the phosphor protection film, the barrier film may include a barrier film substrate and an inorganic thin film layer provided on the barrier film substrate.

[0036] In the above-mentioned phosphor protective film, the above-mentioned laminated film may have a functional layer on the surface of one side of the above-mentioned peeling film, and the above-mentioned functional layer may be a layer that performs at least one function selected from the group consisting of preventing interference fringes, anti-reflection function, light scattering function, antistatic function and anti-damage function.

[0037] In addition, the present disclosure provides a phosphor protective film, which comprises: a main body including a support film, and a peeling film that can be peeled off from the main body and is provided on one surface of the main body, and the thickness of the peeling film accounts for more than 50% of the total thickness of the phosphor protective film. According to the phosphor protective film, by having a peelable peeling film, the generation of wrinkles on the phosphor protective film can be sufficiently suppressed. The peeling film is peeled off when manufacturing the wavelength conversion sheet and does not remain in the resulting wavelength conversion sheet, so that it can be ensured that the film has a thickness sufficient to improve the wrinkles. In particular, by having a thickness of the peeling film that is more than 50% of the total thickness of the phosphor protective film, the effect of suppressing the generation of wrinkles on the phosphor protective film can be sufficiently obtained. In addition, the wavelength conversion sheet obtained using the phosphor protective film can be sufficiently thinned.

[0038] In addition, the present disclosure provides a wavelength conversion sheet with a release film, which is constructed to have two sheets of the above-mentioned phosphor protective films of the present disclosure, and a phosphor layer containing a phosphor is sandwiched between the two sheets of the phosphor protective films, and the two sheets of the above-mentioned phosphor protective films are configured in a manner such that the above-mentioned release film becomes the outermost layer.

[0039] In addition, the present disclosure provides a wavelength conversion sheet obtained by peeling off the above-mentioned peeling film from the wavelength conversion sheet with peeling film of the present disclosure. The above-mentioned wavelength conversion sheet is obtained by using the above-mentioned phosphor protection film of the present disclosure and the wavelength conversion sheet with peeling film using the phosphor protection film, thereby achieving sufficient thinning and sufficiently suppressing the generation of wrinkles.

[0040] Effects of the Invention

[0041] According to the present disclosure, a method for manufacturing a wavelength conversion sheet, a phosphor protective film, a wavelength conversion sheet with a release film, and a wavelength conversion sheet can be provided, which can realize thin filmization of the wavelength conversion sheet and suppress the generation of wrinkles on the phosphor protective film, thereby suppressing the uneven light emission of the phosphor caused by the wrinkles.

[0042] BRIEF DESCRIPTION OF THE DRAWINGS

[0043] [ Figure 1 ] is a schematic cross-sectional view showing an embodiment of a phosphor protection film according to the present disclosure.

[0044] [ Figure 2 ] is a schematic cross-sectional view showing another embodiment of the phosphor protection film according to the present disclosure.

[0045] [ Figure 3 ] is a schematic cross-sectional view showing an embodiment of a wavelength conversion sheet with a release film according to the present disclosure.

[0046] [ Figure 4 ] is a schematic cross-sectional view showing another embodiment of a wavelength conversion sheet with a release film according to the present disclosure.

[0047] [ Figure 5 ] is a schematic cross-sectional view showing an embodiment of a wavelength conversion plate according to the present disclosure.

[0048] [ Figure 6 ] is a schematic cross-sectional view showing another embodiment of the wavelength conversion plate according to the present disclosure.

[0049] [ Figure 7 ] is a schematic cross-sectional view showing an embodiment of a light-emitting unit according to the present disclosure.

[0050] [ Figure 8] is a schematic cross-sectional view showing another embodiment of the phosphor protection film according to the present disclosure. DETAILED DESCRIPTION

[0051] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings as appropriate. It should be noted that in the accompanying drawings, the same or corresponding parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.

[0052] <Phosphor protection film and method for producing the same>

[0053] The phosphor protection film according to the present embodiment comprises: a laminated film having a barrier film, and a release film provided on one surface of the laminated body and capable of being peeled off from the laminated film. Here, the laminated film may have a functional layer on the surface of the release film side. The release film may be attached to the laminated film via an adhesive layer. The barrier film may have a structure in which an inorganic thin film layer is formed on a barrier film substrate, or may have a structure in which a gas barrier coating layer is further formed on the inorganic thin film layer.

[0054] Figure 1 FIG. 2 is a schematic cross-sectional view showing one embodiment of a phosphor protection film. Figure 1 As shown, the phosphor protection film 100 has a structure in which a laminated film 50 composed of a barrier film 10 and a functional layer 40 and a release film 70 are bonded together via an adhesive layer 60. In the phosphor protection film 100, the laminated film 50 has only the functional layer 40 between the barrier film 10 and the release film 70 without having a support film (resin film).

[0055] In the phosphor protection film 100 , the barrier film 10 has a structure in which an inorganic thin film layer 12 and a gas barrier coating layer 13 are sequentially stacked on a barrier film substrate 11 .

[0056] In the phosphor protection film 100 , the release film 70 is composed of a single-layer resin film. However, the release film 70 may be a multi-layer film in which a plurality of resin films are stacked.

[0057] In the phosphor protection film 100, the functional layer 40 can be formed by coating a coating on the barrier film 10 or laminating a vapor-deposited film on the barrier film 10. The functional layer 40 formed of a coating film formed of a coating or a vapor-deposited film can impart optical or mechanical functions.

[0058] In the phosphor protective film 100, preferably, the thickness of the stripping film 70 accounts for more than 50% of the thickness (total thickness) of the phosphor protective film 100. If the thickness of the stripping film 70 accounts for more than 50% of the total thickness of the phosphor protective film 100, the influence of the stripping film 70 is dominant, and wrinkles can be more fully prevented from being generated on the phosphor protective film 100. From the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 100, the thickness of the stripping film 70 accounts for more than 60% of the total thickness of the phosphor protective film 100, and more preferably more than 70%. On the other hand, from the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 100 and inhibiting the total thickness of the phosphor protective film 100 from becoming too thick, the thickness of the stripping film 70 is preferably less than 90%, and more preferably less than 86%. It should be noted that the thickness (total thickness) of the phosphor protective film 100 can be 50μm to 300μm.

[0059] Figure 2 FIG. 2 is a schematic cross-sectional view showing another embodiment of a phosphor protection film. Figure 2 As shown, the phosphor protection film 110 has a structure in which a laminated film 50 composed of a barrier film 10, an adhesive layer 20, a support film 30, and a functional layer 40 is bonded to a release film 70 via an adhesive layer 60. The layer structure of the phosphor protection film 110 is different from that of the phosphor protection film 100 in that in the phosphor protection film 110, the laminated film 50 has a support film (resin film) 30 bonded to the barrier film 10 via an adhesive layer 20 between the barrier film 10 and the functional layer 40.

[0060] In the phosphor protection film 110 , the functional layer 40 may be formed by applying a coating material on the support film 30 or by laminating a vapor-deposited film on the support film 30 .

[0061] In the phosphor protective film 110, preferably, the total thickness of the support film 30 and the release film 70 accounts for more than 60% of the thickness (total thickness) of the phosphor protective film 110. If the total thickness of the support film 30 and the release film 70 accounts for more than 60% of the total thickness of the phosphor protective film 110, the generation of wrinkles can be more fully prevented. From the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 110, the total thickness of the support film 30 and the release film 70 accounts for preferably more than 60% of the total thickness of the phosphor protective film 110, and more preferably more than 70%. On the other hand, from the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 110 and suppressing the total thickness of the phosphor protective film 110 from becoming too thick, the total thickness of the support film 30 and the release film 70 accounts for preferably less than 90% of the total thickness of the phosphor protective film 110, and more preferably less than 86%. It should be noted that the thickness (total thickness) of the phosphor protection film 110 may be 50 μm to 300 μm.

[0062] Hereinafter, each layer constituting the phosphor protection films 100 and 110 will be described in detail.

[0063] The barrier film substrate 11 is not particularly limited, but a film having a total light transmittance of 85% or more is desirable. For example, a polyethylene terephthalate film, a polyethylene naphthalate film, or the like can be used as a substrate having high transparency and excellent heat resistance. The thickness thereof is, for example, 9 μm to 50 μm, preferably 12 μm to 30 μm, and more preferably 12 μm to 25 μm. If the thickness of the barrier film substrate 11 is 9 μm or more, the strength of the barrier film substrate 11 can be sufficiently ensured, while if it is 50 μm or less, long bundles can be manufactured efficiently and economically.

[0064] Next, the inorganic thin film layer 12 is not particularly limited, and for example, aluminum oxide, silicon oxide, magnesium oxide, or a mixture thereof can be used. Among them, aluminum oxide or silicon oxide is preferably used from the viewpoint of barrier properties and productivity.

[0065] Then, the thickness (film thickness) of the inorganic thin film layer 12 is preferably set in the range of 5nm to 500nm, and more preferably in the range of 10nm to 100nm. If the film thickness is 5nm or more, it tends to be easy to form a uniform film and more fully play the function as a gas barrier material. On the other hand, if the film thickness is 500nm or less, it tends to be able to keep the film more flexible, and it can more reliably prevent the film from cracking due to external reasons such as bending and pulling after film formation.

[0066] The gas barrier coating layer 13 is provided to prevent various secondary damages in the subsequent steps and to impart high barrier properties. From the viewpoint of obtaining excellent barrier properties, the gas barrier coating layer 13 preferably contains at least one selected from the group consisting of a hydroxyl-containing polymer compound, a metal alkoxide, a metal alkoxide hydrolyzate, and a metal alkoxide polymer as a component. In addition, the gas barrier coating layer 13 may further contain a silane coupling agent.

[0067] Specific examples of the hydroxyl-containing polymer compound include water-soluble polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, and starch. In particular, when polyvinyl alcohol is used, the barrier properties are most excellent.

[0068] Metal alkoxides are of the general formula: M(OR) n (M represents a metal atom such as Si, Ti, Al, Zr, etc., R represents an alkyl group such as -CH3, -C2H5, and n represents an integer corresponding to the valence of M). Specifically, tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-iso-C3H7)3], etc. can be listed. Tetraethoxysilane and triisopropoxyaluminum are relatively stable in aqueous solvents after hydrolysis, so they are preferred. In addition, as hydrolyzates and polymers of metal alkoxides, for example, as hydrolyzates or polymers of tetraethoxysilane, silicic acid (Si(OH)4) and the like can be listed, and as hydrolyzates or polymers of tripropoxyaluminum, aluminum hydroxide (Al(OH)3) and the like can be listed. In addition, as silane coupling agents, those represented by the general formula: R 1 Si(OR 2 ) n (R 1 : Organic functional group, R 2 :CH3, C2H5 and other alkyl groups). Specifically, silane coupling agents such as ethyltrimethoxysilane, vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane can be listed. In addition, in the gas barrier coating layer 13, isocyanate compounds, or known additives such as dispersants, stabilizers, viscosity modifiers, and colorants can be added as needed within the range that does not damage its gas barrier properties.

[0069] The thickness (film thickness) of the gas barrier coating layer 13 is preferably set in the range of 50nm to 1000nm, and more preferably in the range of 100nm to 500nm. If the film thickness is 50nm or more, it tends to be possible to obtain more sufficient gas barrier properties, and if it is 1000nm or less, it tends to be possible to keep the film more flexible.

[0070] The support film 30 is not particularly limited, but is preferably a resin film having a total light transmittance of 85% or more. For example, a polyethylene terephthalate film, a polyethylene naphthalate film, or the like can be used as a resin film having high transparency and excellent heat resistance.

[0071] Preferably, the thickness of the support film 30 is determined in consideration of the thickness of the barrier film 10, the thickness of the adhesive layer 20, the thickness of the peeling film 70, etc., so that the total thickness of the support film 30 and the peeling film 70 accounts for 60% or more of the total thickness of the phosphor protective film 110. The thickness of the support film 30 is, for example, 12 μm to 150 μm, preferably 25 μm to 120 μm, and more preferably 35 μm to 100 μm. When the total thickness of the support film 30 and the peeling film 70 accounts for 60% or more of the total thickness of the phosphor protective film 110, the strength required for improving the wrinkles of the phosphor protective film 110 can be sufficiently ensured, and when the thickness of the support film 30 is 150 μm or less, it is easy to prevent the total thickness of the phosphor protective film 110 from becoming too thick. In addition, from the viewpoint of thinning the wavelength conversion sheet, the thickness of the support film 30 is preferably less than the thickness of the peeling film 70, and more preferably less than 2 / 3 of the thickness of the peeling film 70.

[0072] As the functional layer 40, for example, a coating film composed of a binder resin and microparticles can be used. In addition, microparticles can be embedded in the binder resin in a manner that a portion of the microparticles is exposed from the surface of the functional layer 40, thereby generating tiny bumps on the surface of the functional layer 40. In this way, by providing the functional layer 40 on the surface of the laminated film 50 (i.e., the surface of the wavelength conversion plate), the generation of interference fringes such as Newton rings can be more fully prevented. In addition, the incident light is scattered to exert a light scattering function, and at the same time, an anti-reflection function can also be exerted.

[0073] As the binder resin, there is no particular limitation, and resins with excellent optical transparency can be used. More specifically, for example, thermoplastic resins, thermosetting resins, ionizing radiation curing resins, etc. such as polyester resins, acrylic resins, acrylic carbamate resins, polyester acrylate resins, polyurethane acrylate resins, carbamate resins, epoxy resins, polycarbonate resins, polyamide resins, polyimide resins, melamine resins, and phenolic resins can be used. Among them, it is desirable to use acrylic resins with excellent light resistance and optical properties. The above-mentioned resins can be used only one, or a plurality of them can be used in combination. In addition, by using thermosetting resins or ionizing radiation curing resins, etc., it is possible to play an anti-damage function.

[0074] The microparticles are not particularly limited, and for example, inorganic microparticles such as silicon dioxide, clay, talc, calcium carbonate, calcium sulfate, barium sulfate, titanium oxide, and aluminum oxide, and organic microparticles such as styrene resin, urethane resin, silicone resin, and acrylic resin can be used. The above microparticles can be used alone or in combination of multiple types.

[0075] The average particle size of the microparticles is preferably 0.1 μm to 30 μm, more preferably 0.5 μm to 10 μm. If the average particle size of the microparticles is 0.1 μm or more, an excellent interference fringe prevention function tends to be obtained, and if it is 30 μm or less, the transparency tends to be further improved. Based on the total amount of the functional layer 40, the content of the microparticles in the functional layer 40 is preferably 0.5 mass % to 30 mass %, more preferably 3 mass % to 10 mass %. If the content of the microparticles is 0.5 mass % or more, the light scattering function and the effect of preventing the generation of interference fringes tend to be further improved, and if it is 30 mass % or less, the reduction in brightness tends to be fully suppressed.

[0076] The thickness of the functional layer 40 is preferably 0.1 μm to 20 μm, more preferably 0.3 μm to 10 μm. When the thickness of the functional layer 40 is 0.1 μm or more, a uniform film tends to be easily obtained, and at least one function selected from the group consisting of the interference fringe prevention function, the reflection prevention function, the light scattering function, the antistatic function, and the damage prevention function is easily obtained. On the other hand, when the thickness of the functional layer 40 is 20 μm or less, when fine particles are used in the functional layer 40, the fine particles are exposed on the surface of the functional layer 40, and the concavoconvex effect tends to be easily obtained.

[0077] Next, as the adhesive or adhesive constituting the adhesive layer 20, acrylic adhesives, epoxy adhesives, urethane adhesives, etc. can be listed. The adhesive preferably contains epoxy resin. By containing epoxy resin in the adhesive, the adhesion between the barrier film 10 and the support film 30 can be improved. As the adhesive, acrylic adhesives, polyvinyl ether adhesives, urethane adhesives, silicone adhesives, starch paste adhesives, etc. can be listed. The thickness of the adhesive layer 20 is preferably 0.5μm to 50μm, more preferably 1μm to 20μm, and further preferably 2μm to 6μm. By having a thickness of the adhesive layer 20 of 0.5μm or more, it is easy to obtain the adhesion between the barrier film 10 and the support film 30, and by being 50μm or less, it is easy to obtain a better gas barrier property.

[0078] It should be noted that the oxygen permeability of the adhesive layer 20 is, for example, 1000 cm in the thickness direction when the thickness is 5 μm. 3 / (m 2 The above oxygen permeability is preferably 500cm3 / (m 2 ·day·atm) or less, more preferably 100cm 3 / (m 2 ·day·atm) or less, more preferably 50cm 3 / (m 2 ·day·atm) or less, particularly preferably 10cm 3 / (m 2 ·day·atm) or less. By making the oxygen permeability of the adhesive layer 20 1000cm 3 / (m 2 ·day·atm) or less, even if the inorganic thin film layer 12 or the gas barrier coating layer 13 has defects, it is possible to obtain a phosphor protection film 110 that can suppress black spots. The lower limit of the above oxygen permeability is not particularly limited, but is, for example, 0.1 cm 3 / (m 2 ·day·atm).

[0079] Preferably, the release film 70 is a resin film that can smooth out wrinkles generated during the manufacturing process of the barrier film 10 and has an elastic modulus sufficient to suppress the generation of further wrinkles. From this point of view, as the release film 70, polyethylene terephthalate film, polyethylene naphthalate film, polypropylene film, etc. can be used. Among them, polyethylene terephthalate film is preferred because it can more fully suppress the generation of wrinkles. The release film 70 can be composed of a resin film with a single-layer structure, or it can be composed of a resin film with a multi-layer structure in which a plurality of resin films are stacked. In addition, the release film 70 also has a protective function of protecting the laminated film 50 from damage such as scratches. Therefore, when the phosphor protection films 100 and 110 are used or when the wavelength conversion sheet is manufactured, the release film 70 can prevent the laminated film 50 from being damaged.

[0080] The peeling film 70 may be colored. In this case, the recognition of the peeling film 70 can be improved, and it can be easily peeled off when manufacturing the wavelength conversion sheet, and it can prevent forgetting to peel off. The peeling film 70 will eventually be peeled off and removed, and it is not necessary to be transparent, so it has the advantage of being able to be colored. In addition, from the same point of view, the peeling film 70 may be opaque or translucent, and may be printed, painted, or patterned.

[0081] Preferably, the thickness of the release film 70 is adjusted so that the ratio of the thickness of the release film 70 alone to the total thickness of the phosphor protection film 100 is 50% or more. The thickness of the release film 70 in the phosphor protection film 100 is, for example, 25 μm to 250 μm, preferably 50 μm to 230 μm, more preferably 60 μm to 200 μm, and further preferably 75 μm to 180 μm. When the thickness of the release film 70 accounts for more than 50% of the total thickness of the phosphor protection film 100, the strength required to obtain the effect of improving the wrinkles of the phosphor protection film 100 can be fully ensured. When the thickness of the release film 70 is 250 μm or less, it is easy to prevent the total thickness of the phosphor protection film 100 from becoming too thick.

[0082] Preferably, the thickness of the release film 70 is adjusted so that the total thickness of the support film 30 and the release film 70 accounts for more than 60% of the total thickness of the phosphor protective film 110. The thickness of the release film 70 in the phosphor protective film 110 is, for example, 25 μm to 250 μm, preferably 30 μm to 230 μm, more preferably 40 μm to 200 μm, and further preferably 50 μm to 180 μm. By making the total thickness of the support film 30 and the release film 70 account for more than 60% of the total thickness of the phosphor protective film 110, the strength required to obtain the effect of improving the wrinkles of the phosphor protective film 110 can be fully ensured. By making the thickness of the release film 70 less than 250 μm, it is easy to prevent the total thickness of the phosphor protective film 110 from becoming too thick.

[0083] The tensile modulus of the release film 70 is preferably 290 MPa or more, more preferably 290 MPa to 380 MPa. By having a tensile modulus of 290 MPa or more, the effect of improving the wrinkles of the phosphor protective films 100 and 110 can be more fully obtained. In this specification, the tensile modulus of the release film 70 is measured by using a test piece obtained by punching the release film 70 into a size of 15 mm in width and 100 mm in length. The measuring device used was Autograph AG-X (manufactured by Shimadzu Corporation), and the measurement was performed under the conditions of a tensile speed of 300 mm / min, a temperature of 25°C, and a humidity of 40% RH.

[0084] If necessary, the release film 70 may contain additives such as an antistatic agent, an ultraviolet absorber, a plasticizer, and a lubricant. In addition, at least one surface of the release film 70 may be subjected to a corona treatment, a flame treatment, a plasma treatment, or the like.

[0085] The adhesive layer 60 is provided to hold the release film 70 in a state of being attached to the laminate film 50. When the release film 70 is peeled off from the laminate film 50, the adhesive layer 60 is also peeled off together with the release film 70. It should be noted that when the release film 70 is a self-adhesive film or the like that can be closely attached to the laminate film 50 without the adhesive layer 60, the adhesive layer 60 is not required. Examples of the adhesive constituting the adhesive layer 60 include acrylic adhesives, polyvinyl ether adhesives, urethane adhesives, silicone adhesives, starch paste adhesives, and the like.

[0086] The thickness of the adhesive layer 60 is preferably 0.5 μm to 20 μm, more preferably 1 μm to 10 μm, and further preferably 1 μm to 5 μm. When the thickness of the adhesive layer 60 is 0.5 μm or more, it is easy to obtain the close adhesion between the release film 70 and the laminated film 50, and when it is 20 μm or less, it is easy to obtain the wrinkle improvement effect of the phosphor protection film 100, 110, and it is easy to suppress the adhesive layer 60 from remaining on the laminated film 50 when the adhesive layer 60 and the release film 70 are peeled off from the laminated film 50.

[0087] The adhesive force between the adhesive layer 60 and the release film 70 is preferably greater than the adhesive force between the adhesive layer 60 and the laminated film 50. Thus, the adhesive layer 60 can be easily peeled off from the laminated film 50 together with the release film 70. As a method for making the adhesive force between the adhesive layer 60 and the release film 70 greater than the adhesive force between the adhesive layer 60 and the laminated film 50, a method such as applying corona treatment to the adhesive-coated surface of the release film 70 can be cited.

[0088] In this specification, the so-called release film 70 can be peeled off from the laminated film 50, which means that the release film 70 can be peeled off from the laminated film 50 together with the adhesive layer 60 when there is an adhesive layer 60 without damaging the laminated film 50. From the viewpoint that the release film with an adhesive layer can be easily peeled off from the laminated film 50, the adhesive force between the release film with an adhesive layer and the laminated film 50 (in this embodiment, between the adhesive layer 60 and the functional layer 40) is preferably 1.0N / 25mm or less, and more preferably 0.7N / 25mm or less. From the viewpoint of being easy to further improve wrinkles, the adhesive force is preferably 0.05N / 25mm or more, and more preferably 0.1N / 25mm or more. The adhesive force is a value measured by the following method. That is, for a test sample obtained by cutting the phosphor protective film into a predetermined size (e.g., 25 mm×100 mm), the peeling force required to peel the peeling film with the adhesive layer from the laminate film 50 was measured using Autograph AG-X (Shimadzu Corporation). The measurement conditions were T-type peeling, a tensile speed of 300 mm / min, and an atmosphere of 25° C. and 40% RH.

[0089] The phosphor protection films 100 and 110 can be manufactured by a roll-to-roll method through the following steps. That is, first, a roll of a barrier film substrate 11 is prepared, and while the barrier film substrate 11 is unwound and conveyed from the roll, an inorganic thin film layer 12 is stacked on the barrier film substrate 11, or an inorganic thin film layer 12 and a gas barrier coating layer 13 are stacked in sequence to manufacture a long strip of barrier film 10 and then rolled up. Next, in the case of stacking a support film 30, while the barrier film 10 is unwound and conveyed, an adhesive is applied to the gas barrier coating layer 13 to form an adhesive layer 20, and the support film 30 is overlapped on the adhesive layer 20 and pressed, thereby obtaining a barrier film with a support film attached. Then, a functional layer 40 is formed on the barrier film substrate 11 of the barrier film 10, or on the support film 30 of the barrier film with a support film attached, thereby obtaining a laminated film 50.

[0090] Next, while the release film 70 is unwound and conveyed, an adhesive is applied to the release film 70 to form an adhesive layer 60 , and the rolled laminated film 50 is overlapped on the adhesive layer 60 and pressure-bonded, thereby obtaining the phosphor protection films 100 , 110 .

[0091] When the inorganic thin film layer 12 is formed on the barrier film substrate 11, in order to improve the adhesion between the two, an anchor coating can be provided between the two. As the anchor coating, a barrier layer that prevents moisture and oxygen from passing through can be used. The anchor coating can be formed by using a resin selected from (for example) polyester resins, isocyanate resins, carbamate resins, acrylic resins, polyvinyl alcohol resins, ethylene vinyl alcohol resins, vinyl modified resins, epoxy resins, oxazoline-containing resins, modified styrene resins, modified silicone resins or alkyl titanates. The anchor coating can be formed by using the above resins alone, or it can be formed by using a composite resin obtained by combining two or more of the above resins. It should be noted that as a method for forming the inorganic thin film layer 12, a so-called vapor deposition method can be used. As vapor deposition methods, vacuum evaporation, sputtering, ion plating, etc. can be listed. It should be noted that in the step of forming the inorganic thin film layer 12, sometimes tension is applied to the barrier film substrate 11 or heat is applied. Then, due to the tension or heat, wrinkles may be generated in the barrier film substrate 11 .

[0092] Next, the gas barrier coating layer 13 can be formed by, for example, coating an aqueous solution or a water / alcohol mixed solution containing at least one component selected from the group consisting of metal alkoxides, metal alkoxide hydrolyzates, and metal alkoxide polymers, a hydroxyl-containing polymer compound, and, if necessary, a silane coupling agent on the surface of the inorganic thin film layer 12, and heating and drying the solution at, for example, 80° C. to 250° C. In the step of forming the gas barrier coating layer 13, tension is also applied to the barrier film substrate 11. The tension and heating and drying may cause wrinkles in the barrier film substrate 11.

[0093] The temperature during the heating and drying in the step of forming the gas barrier coating layer 13 is preferably 210°C or less, and more preferably 180°C or less. By setting the temperature to 210°C or less, the value of the wrinkle coefficient α can be made smaller. On the other hand, the temperature during the heating and drying is preferably 120°C or more, and more preferably 150°C or more. By setting the temperature to 120°C or more, the water vapor barrier property can be further improved.

[0094] Then, in the case of laminating the support film 30, the bonding between the barrier film 10 and the support film 30 can be performed by using a laminating device in a roll-to-roll manner. That is, the support film 30 is unwound from the roller of the support film 30, and an adhesive (or adhesive) is coated on the support film 30 by an adhesive coating device to form an adhesive layer 20. Next, the support film 30 formed with the adhesive layer 20 is guided into an oven by a guide roller to dry the adhesive layer 20. For the temperature in the oven, a plurality of units can be used to change the temperature in stages, and can be set to 25°C to 200°C respectively. After drying, the support film 30 is conveyed to a nip roller by guiding it through a guide roller. On the other hand, the barrier film 10 is unwound from the roller of the barrier film 10 and conveyed to a nip roller, and is pressed onto the adhesive-coated surface of the support film 30 by a nip roller for bonding. The lamination pressure between the nip rolls can be set to, for example, 0.05 MPa to 0.2 MPa. Then, the obtained barrier film with the support film is wound up in a roll. According to this method, the support film 30 is laminated on the barrier film 10, thereby reducing heat wrinkles.

[0095] In the step of laminating the support film 30 and the barrier film 10 via the adhesive layer 20 , when the support film 30 and the barrier film 10 are pressed and bonded by a nip roll, the barrier film 10 with wrinkles eliminated is held on the support film 30 , thereby reducing wrinkles.

[0096] Next, the functional layer 40 can be formed by, for example, applying a coating liquid containing a binder resin and microparticles onto the surface of the barrier film substrate 11 or the support film 30, and drying and curing. Examples of the coating method include coating methods using a gravure coater, a dip coater, a reverse coater, a wire bar coater, and a die coater. As described above, the functional layer 40 can be formed on the support film 30 in advance before the barrier film 10 and the support film 30 are bonded together.

[0097] Then, the bonding between the release film 70 and the laminate film 50 can be performed by using a laminating device in a roll-to-roll manner. That is, the release film 70 is unwound from the roller of the release film 70, and the adhesive is applied to the release film 70 by an adhesive coating device to form an adhesive layer 60. Next, the laminate film 50 formed with the adhesive layer 60 is guided into an oven by a guide roller to dry the adhesive layer 60. For the temperature in the oven, a plurality of units can be used to change the temperature in stages, and can be set to 25°C to 200°C respectively. After drying, the release film 70 is conveyed to the nip roller by guiding the guide roller. On the other hand, the laminate film 50 is unwound from the roller of the laminate film 50 and conveyed to the nip roller, and the nip roller is pressed onto the adhesive-coated surface of the release film 70 for bonding. The lamination pressure between the nip rollers can be set, for example, to 0.05MPa to 0.5MPa. Then, the obtained phosphor protection films 100 and 110 are wound up in a roll shape. According to this method, by laminating the release film 70 on the laminated film 50, the phosphor protection films 100 and 110 with sufficiently reduced heat wrinkles can be obtained.

[0098] In the step of attaching the release film 70 and the laminated film 50 via the adhesive layer 60, when the release film 70 and the laminated film 50 are pressed by the nip roller, the laminated film 50 in a state where wrinkles have been eliminated is held on the release film 70, thereby reducing wrinkles. The above-mentioned wrinkle reduction effect can be more fully obtained by setting the thickness of the release film 70 or the total thickness of the release film 70 and the support film 30 to be 60% or more of the total thickness of the phosphor protection film 100 or the total thickness of the phosphor protection film 110.

[0099] The phosphor protective film according to the present embodiment may include: a main body including a support film, and a peeling film which is provided on one surface of the main body and can be peeled off from the main body. Here, the main body may include a functional layer on the surface of one side of the peeling film. The peeling film may be attached to the main body via an adhesive layer. The main body may include a primer layer for improving the adhesion with the phosphor layer. In the present embodiment, the main body may not have a barrier film. In the phosphor protective film of such a structure, the thickness of the peeling film is set to be more than 50% of the total thickness of the phosphor protective film. The phosphor protective film of such a structure is useful when the phosphor layer itself has high durability, and since a barrier film is not required, it can be further thinned.

[0100] Figure 8 FIG. 2 is a schematic cross-sectional view showing another embodiment of a phosphor protection film. Figure 8 As shown, the phosphor protection film 120 has a structure in which a main body portion 55 composed of a support film 30 , a functional layer 40 , and a primer layer 80 and a release film 70 are bonded together via an adhesive layer 60 .

[0101] As the support film 30 , the functional layer 40 , and the release film 70 in the phosphor protection film 120 , the same support film 30 , the functional layer 40 , and the release film 70 as those in the phosphor protection films 100 and 110 can be used.

[0102] In the phosphor protection film 120, the thickness of the support film 30 is preferably 12 μm to 50 μm, more preferably 12 μm to 25 μm, and further preferably 12 μm to 15 μm. When the thickness of the support film 30 is 50 μm or less, the wavelength conversion sheet can be further thinned. In addition, when the thickness of the support film 30 is 12 μm or more, the strength of the support film 30 can be sufficiently ensured.

[0103] In the phosphor protection film 120, the thickness of the peeling film 70 is preferably determined in consideration of the thickness of each layer constituting the phosphor protection film 120 so that the ratio of the thickness of the peeling film 70 to the total thickness of the phosphor protection film 120 is 50% or more. The thickness of the peeling film 70 is, for example, 25 μm to 150 μm, preferably 50 μm to 150 μm, and more preferably 75 μm to 150 μm. When the thickness of the peeling film 70 accounts for 50% or more of the total thickness of the phosphor protection film 120, the strength required to obtain the effect of improving the wrinkles of the phosphor protection film 120 can be sufficiently ensured, and when the thickness of the peeling film 70 is 150 μm or less, it is easy to prevent the total thickness of the phosphor protection film 120 from becoming too thick.

[0104] In the phosphor protective film 120, the thickness of the release film 70 preferably accounts for more than 60% of the thickness (total thickness) of the phosphor protective film 120. If the thickness of the release film 70 accounts for more than 60% of the total thickness of the phosphor protective film 120, wrinkles can be more fully prevented. From the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 120, the thickness of the release film 70 accounts for more than 70% of the total thickness of the phosphor protective film 120. On the other hand, from the viewpoint of more fully obtaining the wrinkle improvement effect of the phosphor protective film 120 and suppressing the total thickness of the phosphor protective film 120 from becoming too thick, the thickness of the release film 70 accounts for less than 90% of the total thickness of the phosphor protective film 120, and more preferably less than 86%. It should be noted that the thickness (total thickness) of the phosphor protective film 120 can be 40μm to 170μm.

[0105] The primer layer 80 is a layer for improving the adhesion between the main body 55 and the phosphor layer, and can be formed using, for example, a primer layer-forming composition containing a silane coupling agent. The thickness of the primer layer 80 is, for example, 0.001 μm to 1 μm.

[0106] The phosphor protection film 120 can be manufactured by the same method as that used to manufacture the phosphor protection films 100 and 110 , except that the laminated film 50 is replaced by the main body 55 .

[0107] In the phosphor protection films 100, 110, and 120, the deviation (3σ) of the total thickness of the laminated film 50 or the main body 55 may be 1.5 μm or more, and the coefficient of dynamic friction on the surface of the functional layer 40 may be 0.4 or less. By setting the deviation (3σ) of the total thickness of the laminated film 50 or the main body 55 including the functional layer to 1.5 μm or more, and setting the coefficient of dynamic friction on the surface of the functional layer 40 to 0.4 or less, it is possible to prevent damage to the light guide plate in contact with the wavelength conversion sheet when the wavelength conversion sheet is assembled in a display. From the viewpoint of more fully obtaining the effect of preventing damage to the light guide plate, the deviation (3σ) of the total thickness of the laminated film 50 or the main body 55 may be 1.7 μm or more or 2.0 μm or more.

[0108] In addition, the deviation (3σ) of the total thickness of the phosphor protective films 100, 110, and 120 can be 1.0 μm or less. By making the deviation (3σ) of the total thickness of the phosphor protective films 100, 110, and 120 1.0 μm or less, a wavelength conversion plate with reduced thickness deviation of the phosphor layer can be manufactured. As a result, the occurrence of uneven color development caused by the thickness deviation of the phosphor layer can be suppressed. From the viewpoint of more fully obtaining the above-mentioned effects, the deviation (3σ) of the total thickness of the phosphor protective films 100, 110, and 120 can be 0.8 μm or less or 0.5 μm or less.

[0109] The deviation (3σ) of the total thickness of the laminated film 50 or the main body 55 and the deviation (3σ) of the total thickness of the phosphor protection films 100, 110, and 120 can be measured, for example, using a contact film thickness meter. In addition, the dynamic friction coefficient of the surface of the functional layer 40 can be measured, for example, using Autograph AG-X (Shimadzu Corporation).

[0110] In the phosphor protection films 100, 110, and 120, the peel strength between the laminate film 50 or the main body 55 and the release film 70 based on JIS K6854-3 can be 0.05N / 25mm to 1.5N / 25mm, or 0.05N / 25mm to 1.0N / 25mm. By the peel strength being within the above range, the presence of the release film 70 can more effectively suppress the generation of wrinkles on the phosphor protection films 100, 110, and 120, and the release film 70 can be smoothly peeled off from the laminate film 50 or the main body 55 in the peeling step. In addition, the release film 70 is attached to the laminate film 50 or the main body 55 via the adhesive layer 60, and by the peel strength being 0.05N / 25mm or more, it can be suppressed that a portion of the adhesive layer 60 remains on the laminate film 50 or the main body 55 after the peeling step. In addition, by setting the peel strength to 1.0 N / 25 mm or less, it is possible to prevent a portion of the functional layer 40 in contact with the adhesive layer 60 from being peeled off together with the peeling film 70 when the peeling film 70 is peeled off. The peel strength can be adjusted to the above range by appropriately adjusting the type and blending amount of the resin and curing agent used in the functional layer 40 and the type of adhesive used in the adhesive layer 60.

[0111] <Wavelength conversion sheet and method for manufacturing the same, and light emitting unit>

[0112] The phosphor protection films 100 , 110 , and 120 can be used as components of a wavelength conversion sheet. The wavelength conversion sheet manufactured in this way can be used as components of a light-emitting unit such as a backlight unit of a liquid crystal display and an electroluminescent unit. Figure 3 2 is a cross-sectional view schematically showing a wavelength conversion sheet 500 with a release film using the phosphor protection film 100. Figure 5 2 is a cross-sectional view schematically showing a wavelength conversion sheet 700 obtained by peeling off the release film 70 and the adhesive layer 60 from the wavelength conversion sheet 500 with the release film. Figure 4 2 is a cross-sectional view schematically showing a wavelength conversion sheet 600 with a release film using a phosphor protection film 110. Figure 6 2 is a cross-sectional view schematically showing a wavelength conversion sheet 800 obtained by peeling off the release film 70 and the adhesive layer 60 from the wavelength conversion sheet 600 with the release film. Figure 7 1 is a cross-sectional view schematically showing a specific example of the light emitting unit. In addition, a wavelength conversion sheet with a release film and a wavelength conversion sheet can also be formed by using the phosphor protection film 120 .

[0113] like Figure 3 As shown in FIG. 1 , the wavelength conversion sheet 500 with a release film includes: a phosphor layer 200, and phosphor protection films 100, 100 respectively provided on both sides of the phosphor layer 200. In this way, the wavelength conversion sheet 500 with a release film is configured such that the phosphor layer 200 is sandwiched (i.e., sealed) between a pair of phosphor protection films 100, 100. Figure 5 As shown, by peeling off the peeling film 70 and the adhesive layer 60 from the wavelength conversion sheet 500 with the peeling film, the target wavelength conversion sheet 700 can be obtained. Figure 4 The wavelength conversion sheet 600 with a release film is shown by Figure 3 The fluorescent material protection film 100 of the wavelength conversion sheet 500 with a release film shown is changed to Figure 2 The fluorescent body protection film 110 shown in FIG. Figure 6 As shown, by peeling off the peeling film 70 and the adhesive layer 60 from the wavelength conversion sheet 600 with the peeling film, the target wavelength conversion sheet 800 can be obtained. In this way, the peeling film 70 and the adhesive layer 60 do not exist in the obtained wavelength conversion sheets 700 and 800, so that the generation of wrinkles can be fully suppressed and the thickness can be sufficiently reduced.

[0114] In the wavelength conversion sheets 500, 600 and the wavelength conversion sheets 700, 800 with release films, a layer (hereinafter referred to as a "primer layer") for improving the adhesion between the phosphor layer 200 and the laminated film 50 may be provided. The thickness of the primer layer is, for example, 0.001 μm to 1 μm. The primer layer can be formed by, for example, using a primer layer forming composition containing a silane coupling agent.

[0115] The phosphor layer 200 is a thin film having a thickness of tens to hundreds of μm and is Figures 3 to 6The figure shows a sealing resin 202 and a phosphor 201. Inside the sealing resin 202, the phosphor 201 is sealed in a state of mixing more than one kind. When the phosphor layer 200 and a pair of phosphor protective films 100, 100 or a pair of phosphor protective films 110, 110 are stacked, the sealing resin 202 plays the role of bonding them together and filling their gaps. The phosphor layer 200 can also be formed by stacking two or more phosphor layers that only seal one kind of phosphor 201. The two or more phosphors 201 used in these one or more phosphor layers are selected to have the same excitation wavelength. The excitation wavelength is selected according to the wavelength of the light irradiated by the light source. The fluorescent colors of the two or more phosphors 201 are different from each other. When two kinds of phosphors 201 are used, each fluorescent color is preferably red and green. The wavelength of each fluorescence and the wavelength of the light irradiated by the light source are selected according to the spectral characteristics of the color filter. Regarding the peak wavelength of fluorescence, for example, red is 610nm and green is 550nm.

[0116] As the sealing resin 202, for example, a thermoplastic resin, a thermosetting resin, an ultraviolet curing resin, or the like can be used. These resins may be used alone or in combination of two or more.

[0117] As thermoplastic resins, for example, cellulose derivatives such as cellulose acetate, cellulose nitrate, cellulose acetate butyrate, ethyl cellulose and methyl cellulose; vinyl resins such as vinyl acetate and its copolymers, vinyl chloride and its copolymers, and vinylidene chloride and its copolymers; acetal resins such as polyvinyl formal and polyvinyl butyral; acrylic resins such as acrylic resin and its copolymers, methacrylic resin and its copolymers; polystyrene resins; polyamide resins; linear polyester resins; fluororesins; and polycarbonate resins.

[0118] Examples of the thermosetting resin include phenol resin, urea melamine resin, polyester resin, and silicone resin.

[0119] Examples of the ultraviolet curable resin include photopolymerizable prepolymers such as epoxy acrylate, urethane acrylate, and polyester acrylate. Alternatively, the photopolymerizable prepolymer may be used as a main component and a monofunctional or polyfunctional monomer may be used as a diluent.

[0120] As the phosphor 201, quantum dots are preferably used. As quantum dots, for example, a substance in which a core as a light-emitting portion is covered with a shell as a protective film can be listed. As the core, for example, cadmium selenide (CdSe) and the like can be listed, and as the shell, for example, zinc sulfide (ZnS) and the like can be listed. The surface defects of CdSe particles are covered by ZnS with a large band gap, thereby improving the quantum efficiency. In addition, the phosphor 201 may also be a structure in which the core is doubly covered with a first shell and a second shell. In this case, CdSe can be used for the core, zinc selenide (ZnSe) can be used for the first shell, and ZnS can be used for the second shell. In addition, as a phosphor 201 other than quantum dots, YAG:Ce and the like can also be used.

[0121] The average particle size of the phosphor 201 is preferably 1 nm to 20 nm. The thickness of the phosphor layer 200 is preferably 1 μm to 500 μm. Based on the total amount of the phosphor layer 200, the content of the phosphor 201 in the phosphor layer 200 is preferably 1 mass % to 20 mass %, more preferably 3 mass % to 10 mass %.

[0122] The wavelength conversion sheet according to the present embodiment can be manufactured by (for example) the following method. First, a phosphor layer forming composition containing a sealing resin 202 and a phosphor 201 is applied to the surface of the first phosphor protection film 100, 110 on the side opposite to the release film 70 (on the gas barrier coating layer 13 or on the barrier film substrate 11), and a curing treatment using heating, ultraviolet irradiation, etc. is performed to form the phosphor layer 200. After the phosphor layer forming composition is applied, the second phosphor protection film 100, 110 is prepared, and pressure is applied in a state where the coating film of the phosphor layer forming composition or the surface of the phosphor layer 200 is in contact with the surface of the second phosphor protection film 100, 110 on the side opposite to the release film 70, so that the first phosphor protection film 100, 110, the phosphor layer 200, and the second phosphor protection film 100, 110 can be stacked without an adhesive layer. The curing treatment using heating, ultraviolet ray irradiation, or the like may be performed before lamination of the second phosphor protection films 100 and 110 , or may be performed after lamination of the second phosphor protection films 100 and 110 .

[0123] There is no particular limitation on the time point for peeling the peeling film 70 and the adhesive layer 60 from the wavelength conversion sheet 500, 600 with a peeling film, and the peeling can be performed at a stage where the wavelength conversion sheet is cut to a size suitable for a display panel and assembled in a light-emitting unit described later. The peeling film 70 is arranged on the outermost surface in advance during the manufacturing step of the wavelength conversion sheet or when the wavelength conversion sheet 500, 600 with a peeling film is cut, so that the wavelength conversion sheet can be prevented from being damaged during the manufacturing step.

[0124] As described above, the wavelength conversion sheets 700 , 800 may be used as components of the light emitting unit 900 .

[0125] like Figure 7 As shown, the light emitting unit 900 includes: a light source 330, a light guide plate 310, and a wavelength conversion sheet 700. Specifically, in the light emitting unit 900, the light guide plate 310 and the reflection plate 320 are sequentially arranged on the surface of one laminate film 50 side, and the light source 330 is arranged on the side of the light guide plate 310. The thickness of the light guide plate 310 is, for example, 100 μm to 1000 μm.

[0126] The light guide plate 310 and the reflector plate 320 effectively reflect the light irradiated by the light source 330 and guide it to the fluorescent layer 200. As the light guide plate 310, for example, acrylic, polycarbonate, and cycloolefin film are used. In the light source 330, for example, a plurality of blue light emitting diode elements are provided. The light emitting diode element may also be a purple light emitting diode or a light emitting diode with a lower wavelength. After the light irradiated by the light source 330 enters the light guide plate 310, it is incident on the fluorescent layer 200 accompanied by reflection and refraction.

[0127] The yellow light generated in the phosphor layer 200 is mixed with the light before passing through the phosphor layer 200, so that the light after passing through the phosphor layer 200 becomes white light. The phosphor layer 200 may be degraded due to contact with oxygen or water vapor for a long time. Figure 7 As shown, it is protected by a pair of laminated films 50, 50. Figure 7 In the embodiment, the wavelength conversion sheet 700 may be replaced with the wavelength conversion sheet 800 or may be replaced with a wavelength conversion sheet formed by using the phosphor protection film 120 .

[0128] Example

[0129] Hereinafter, the present disclosure will be described in more detail based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples. In addition, the peel strength between the release film with an adhesive layer prepared in the Examples and the liner layer was measured by the following method.

[0130] <Measurement of Peel Strength (Adhesion) between Release Film with Adhesive Layer and Backing Layer>

[0131] The release film with the adhesive layer and the laminated film with the liner layer were overlapped in such a way that the liner layer and the adhesive layer were facing each other, and they were pressed by a hot laminator (lamination temperature 40°C, conveying speed 1m / min, lamination pressure 0.5MPa). The adhesive force required for peeling the two test samples after the pressing was measured by Autograph AG-X (manufactured by Shimadzu Corporation). The measurement conditions were set to T-type peeling, a tensile speed of 300mm / min, an atmosphere of 25°C and 40%RH.

[0132] (Example 1)

[0133] The barrier film is prepared as described below. First, silicon oxide is provided as an inorganic thin film layer on one side of a PET film serving as a barrier film substrate by vacuum evaporation, and a gas barrier coating layer is further formed on the inorganic thin film layer. The gas barrier coating layer is formed by applying a coating liquid prepared by mixing tetraethoxysilane and polyvinyl alcohol in a mass ratio of 1:1 by wet coating, and then heating and drying at 180°C for 1 minute. Thus, a barrier film having an inorganic thin film layer and a gas barrier coating layer provided on one side of the substrate is obtained. It should be noted that the thickness of the barrier film is 12.5 μm, the thickness of the barrier film substrate is 12 μm, the thickness of the inorganic thin film layer is 30 nm, and the thickness of the gas barrier coating layer is 0.5 μm.

[0134] Next, a cushion layer forming composition consisting of 100 parts by mass of an acrylic polyol resin (manufactured by DIC Corporation, trade name: OPM adjustment paint), 8.5 parts by mass of an isocyanate curing agent (manufactured by DIC Corporation, trade name: OPM curing agent), 10 parts by mass of fine particles (polyurethane, average particle size 2 μm), and 70 parts by mass of a solvent (ethyl acetate) was applied to the barrier film substrate of the barrier film, and heated and dried at 80° C. for 1 minute to cure, thereby forming a cushion layer with a thickness of 3 μm. Thus, a laminated film having a barrier film and a cushion layer laminated thereon was obtained.

[0135] On the other hand, an adhesive layer-forming composition consisting of 100 parts by mass of an acrylic adhesive (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol MS-3999), 5 parts by mass of an isocyanate curing agent (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol K-315), 2 parts by mass of a stabilizer (acetylacetone), and 221 parts by mass of a solvent (ethyl acetate) was applied to one side of a 50 μm thick PET film as a release film, and then heated and dried at 80° C. for 1 minute to form an adhesive layer with a thickness of 3.5 μm. Thus, a release film with an adhesive layer (peel strength from the backing layer: 0.50 N / 25 mm) was obtained.

[0136] The laminated film and the release film with the adhesive layer were overlapped in the direction where the liner layer and the adhesive layer were in contact, and were pressed by a hot laminator (lamination temperature 40°C, conveying speed 1m / min, lamination pressure 0.5MPa) to obtain a phosphor protective film. The obtained phosphor protective film did not have a support film between the barrier film and the release film, and the thickness of the release film was 72% of the total thickness of the phosphor protective film.

[0137] (Examples 2 to 6)

[0138] The phosphor protective films of Examples 2 to 6 were obtained in the same manner as in Example 1, except that the thickness of the barrier film and the thickness of the release film were respectively changed to the thicknesses shown in Table 1. Here, when the thickness of the barrier film was set to 23.5 μm, the thickness of the inorganic thin film layer and the gas barrier coating layer were not changed, and the thickness of the barrier film substrate was set to 23 μm.

[0139] (Example 7)

[0140] The barrier film was prepared as follows. First, silicon oxide was provided as an inorganic thin film layer on one side of a PET film as a barrier film substrate by vacuum evaporation, and then a gas barrier coating layer was formed on the inorganic thin film layer. The gas barrier coating layer was formed by applying a coating liquid obtained by mixing tetraethoxysilane and polyvinyl alcohol in a mass ratio of 1:1 by wet coating, and then heating and drying at 180°C for 1 minute. Thus, a barrier film having an inorganic thin film layer and a gas barrier coating layer provided on one side of the substrate was obtained. It should be noted that the thickness of the barrier film was 12.5 μm.

[0141] Next, an adhesive layer-forming composition consisting of 100 parts by mass of an acrylic adhesive (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol OC-3405), 1 part by mass of an isocyanate curing agent (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol K-341), and 219 parts by mass of a solvent (toluene) was applied to the gas barrier coating layer of the barrier film, and heated and dried at 80°C for 1 minute to form an adhesive layer. A PET film with a thickness of 25 μm was overlapped on the adhesive layer as a support film, and pressure-bonded by a hot laminator (lamination temperature 40°C, conveying speed 1 m / min, lamination pressure 0.5 MPa). The pressure bonding was performed in a state where the wrinkles of the barrier film were smoothed by clamping. Then, a cushion layer forming composition consisting of 100 parts by mass of an acrylic polyol resin (manufactured by DIC Corporation, trade name: OPM adjustment paint), 8.5 parts by mass of an isocyanate curing agent (manufactured by DIC Corporation, trade name: OPM curing agent), 10 parts by mass of microparticles (polyurethane, average particle size 2 μm), and 70 parts by mass of a solvent (ethyl acetate) was applied on the support film, and heated and dried to cure, thereby forming a cushion layer with a thickness of 3 μm. Thus, a laminated film in which a barrier film, an adhesive layer, a support film, and a cushion layer were laminated in sequence was obtained. In the obtained laminated film, the thickness of the adhesive layer was 5 μm.

[0142] On the other hand, an adhesive layer-forming composition consisting of 100 parts by mass of an acrylic adhesive (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol MS-3999), 5 parts by mass of an isocyanate curing agent (manufactured by Siden Chemical Co., Ltd., trade name: Sibinol K-315), 2 parts by mass of a stabilizer (acetylacetone), and 221 parts by mass of a solvent (ethyl acetate) was applied to one side of a PET film having a thickness of 25 μm as a release film, and then heated and dried at 80° C. for 1 minute to form an adhesive layer having a thickness of 3.5 μm. Thus, a release film having an adhesive layer (peel strength with a backing layer: 0.50 N / 25 mm) was obtained.

[0143] The laminated film and the release film with the adhesive layer were overlapped in the direction where the liner layer and the adhesive layer were in contact, and were pressed by a hot laminator (lamination temperature 40°C, conveying speed 1m / min, lamination pressure 0.5MPa) to obtain a phosphor protective film. The obtained phosphor protective film has a support film between the barrier film and the release film, and the total thickness of the support film and the release film is 68% of the total thickness of the phosphor protective film.

[0144] (Examples 8 to 13)

[0145] The phosphor protection films of Examples 8 to 13 were obtained in the same manner as in Example 7 except that the thickness of the barrier film and the thickness of the release film were respectively changed to the thicknesses shown in Table 1. Here, when the thickness of the barrier film was set to 23.5 μm, the thickness of the inorganic thin film layer and the gas barrier coating layer were not changed, and the thickness of the barrier film substrate was set to 23 μm.

[0146] (Example 14)

[0147] A phosphor protective film was obtained in the same manner as in Example 9 except that a 75 μm-thick PEN film was used as the release film. The peel strength of the release film with an adhesive layer from the cushion layer was 0.16 N / 25 mm.

[0148] (Example 15)

[0149] A phosphor protection film was obtained in the same manner as in Example 10 except that a PEN film having a thickness of 100 μm was used as the release film.

[0150] (Comparative Example 1)

[0151] A phosphor protection film of Comparative Example 1 was obtained in the same manner as in Example 1 except that the release film with the adhesive layer was not laminated.

[0152] (Comparative Example 2)

[0153] A phosphor protection film of Comparative Example 2 was obtained in the same manner as in Example 4 except that the release film with the adhesive layer was not laminated.

[0154] (Comparative Example 3)

[0155] A phosphor protection film of Comparative Example 3 was obtained in the same manner as in Example 7 except that the release film with the adhesive layer was not laminated.

[0156] (Comparative Example 4)

[0157] A phosphor protection film of Comparative Example 4 was obtained in the same manner as in Example 11 except that the release film with the adhesive layer was not laminated.

[0158] <Evaluation of wrinkle degree>

[0159] The phosphor protection films obtained in the examples and comparative examples were visually observed for the presence or absence of wrinkles and their degree, and the degree of wrinkles was evaluated according to the following evaluation criteria. When the evaluation was "D", it was considered unacceptable. The results are shown in Table 1.

[0160] A: No wrinkles were observed.

[0161] B: Shallow and small wrinkles were slightly observed.

[0162] C: Moderate wrinkles were observed.

[0163] D: Deep and large wrinkles were observed.

[0164] [Table 1]

[0165]

[0166] (Example 16)

[0167] A cushion layer forming composition consisting of 100 parts by mass of an acrylic polyol resin (manufactured by DIC Corporation, trade name: OPM adjustment paint), 8.5 parts by mass of an isocyanate curing agent (manufactured by DIC Corporation, trade name: OPM curing agent), 10 parts by mass of microparticles (polyurethane, average particle size 2 μm), and 70 parts by mass of a solvent (ethyl acetate) was applied on a PET film with a thickness of 12.5 μm as a support film, and the composition was heated and dried at 80°C for 1 minute to cure, thereby forming a cushion layer with a thickness of 3 μm. Furthermore, a primer layer-forming composition obtained by diluting 3-aminopropyltriethoxysilane (amine silane coupling agent, manufactured by Shin-Etsu Chemical Co., Ltd., trade name: KBE-903) with ethyl acetate to a solid content of 1.5% was applied on the support film on the side opposite to the liner layer using a wire bar #3, and dried at 120° C. for 1 minute to form a primer layer with a thickness of 30 nm. The support film, the liner layer, and the primer layer were used as the main body. On the other hand, an adhesive layer-forming composition consisting of 100 parts by mass of an acrylic adhesive (manufactured by Saiden Chemical Co., Ltd., trade name: Saibinol MS-3999), 5 parts by mass of an isocyanate curing agent (manufactured by Saiden Chemical Co., Ltd., trade name: Saibinol K-315), 2 parts by mass of a stabilizer (acetylacetone), and 221 parts by mass of a solvent (ethyl acetate) was applied on one side of a PET film having a thickness of 25 μm as a release film, and then heated and dried at 80° C. for 1 minute to form an adhesive layer having a thickness of 5 μm. Thus, a release film having an adhesive layer (peel strength with a support film: 0.08 N / 25 mm) was obtained.

[0168] The main body and the release film with the adhesive layer were overlapped in the direction where the support film and the adhesive layer were in contact, and were pressed by a hot laminator (lamination temperature 40°C, conveying speed 1m / min, lamination pressure 0.5MPa) to obtain a phosphor protective film. In the obtained phosphor protective film, the thickness of the release film was 55% of the total thickness of the phosphor protective film (the total thickness of the support film, the liner layer, the primer layer, the adhesive layer and the release film).

[0169] (Examples 17 to 29 and Comparative Examples 5 to 8)

[0170] Phosphor protection films of Examples 17 to 29 and Comparative Examples 5 to 8 were obtained in the same manner as in Example 16 except that the thickness of the support film and / or the release film was changed to the thickness shown in Table 2.

[0171] <Evaluation of wrinkle degree>

[0172] The phosphor protection films obtained in Examples and Comparative Examples were visually observed for the presence or absence of wrinkles and the extent of the wrinkles, and the extent of the wrinkles was evaluated based on the following evaluation criteria.

[0173] A: No wrinkles were observed.

[0174] B: Shallow and small wrinkles were slightly observed.

[0175] C: Moderate wrinkles were observed.

[0176] D: Deep and large wrinkles were observed.

[0177] [Table 2]

[0178]

[0179] (Example 30)

[0180] The barrier film is prepared as described below. First, silicon oxide is provided as an inorganic thin film layer on one side of a PET film serving as a barrier film substrate by vacuum evaporation, and then a gas barrier coating layer is formed on the inorganic thin film layer. The gas barrier coating layer is formed by applying a coating liquid obtained by mixing tetraethoxysilane and polyvinyl alcohol in a mass ratio of 1:1 by a wet coating method, and then heating and drying at 180°C for 1 minute. Thus, a barrier film having an inorganic thin film layer and a gas barrier coating layer provided on one side of the substrate is obtained. It should be noted that the thickness of the barrier film is 23.5 μm, the thickness of the barrier film substrate is 23 μm, the thickness of the inorganic thin film layer is 30 nm, and the thickness of the gas barrier coating layer is 0.5 μm.

[0181] Next, a cushion layer forming composition consisting of 100 parts by mass of an acrylic polyol resin (manufactured by DIC Corporation, trade name: OPM adjustment paint), 8.5 parts by mass of an isocyanate curing agent (manufactured by DIC Corporation, trade name: OPM curing agent), 10 parts by mass of fine particles (polyurethane, average particle size 2 μm), and 70 parts by mass of a solvent (ethyl acetate) was applied to the barrier film substrate of the barrier film, and heated and dried at 80° C. for 1 minute to cure, thereby forming a cushion layer with a thickness of 3 μm. Thus, a laminated film having a barrier film and a cushion layer laminated thereon was obtained.

[0182] On the other hand, an adhesive layer-forming composition composed of 100 parts by mass of an acrylic adhesive (manufactured by Saiden Chemical Co., Ltd., trade name: Saibinol MS-3999), 5 parts by mass of an isocyanate curing agent (manufactured by Saiden Chemical Co., Ltd., trade name: Saibinol K-315), 2 parts by mass of a stabilizer (acetylacetone), and 221 parts by mass of a solvent (ethyl acetate) was applied to one side of a PET film having a thickness of 75 μm as a release film, and then heated and dried at 80° C. for 1 minute to form an adhesive layer having a thickness of 3.5 μm. Thus, a release film having an adhesive layer (peel strength from a backing layer: 0.50 N / 25 mm) was obtained.

[0183] The laminated film and the release film with the adhesive layer were overlapped in the direction where the liner layer and the adhesive layer were in contact, and were pressed by a hot laminator (lamination temperature 40°C, conveying speed 1m / min, lamination pressure 0.5MPa) to obtain a phosphor protective film. The obtained phosphor protective film did not have a support film between the barrier film and the release film, and the thickness of the release film was 71% of the total thickness of the phosphor protective film.

[0184] (Comparative Example 9)

[0185] A laminated film was prepared as a phosphor protection film by the same method as in Example 30. This phosphor protection film did not include a release film.

[0186] <Measurement of Deviation (3σ) of Total Thickness of Laminated Film and Phosphor Protective Film>

[0187] The film thickness (total thickness) of the laminated film and phosphor protective film obtained in Example 30 and Comparative Example 9 was measured at 50 points at random, and the average value, maximum value, minimum value and deviation (3σ) were obtained. The film thickness was measured using a contact film thickness meter (model: LGF-0110L-B, manufactured by Mitsutoyo Co., Ltd.). The results are shown in Table 3.

[0188] <Measurement of Dynamic Friction Coefficient of Cushion Layer Surface>

[0189] The dynamic friction coefficient of the cushion layer surface in the laminated film obtained in Example 30 and Comparative Example 9 was measured by the following method. The measurement was performed using Autograph AG-X (manufactured by Shimadzu Corporation) in accordance with JIS K7125. The results are shown in Table 3.

[0190] <Evaluation of Uneven Light Emission of Phosphor Layer>

[0191] (Production of wavelength conversion sheet)

[0192] Two sheets of each of the phosphor protective films obtained in Example 30 and Comparative Example 9 were prepared, and a wavelength conversion sheet was made by the following procedure. First, a quantum dot light emitter having a core of cadmium selenide (CdSe) and a shell of zinc sulfide (ZnS) with a particle size of 6 nm, an acrylic photocurable resin having an acryloyl group at the end of the main chain or side chain (produced by Arakawa Chemical, trade name: AP6501), and a photopolymerization initiator (produced by BASF, trade name: Lucirin TPO) was applied on the gas barrier coating layer of a phosphor protective film to form a coating film, and another sheet of phosphor protective film was attached to the coating film with the gas barrier coating layer facing the coating film, and the films were crimped by rollers. An ultraviolet irradiation device was used to irradiate the film at 300 mJ / cm 2 The coating film was exposed to light at an exposure amount of 100 μm to be cured, thereby forming a phosphor layer (thickness 100 μm) having a wavelength conversion function. Subsequently, the release film was peeled off from the backing layer in Example 30. Thus, a wavelength conversion sheet was obtained.

[0193] (Evaluation of uneven light emission)

[0194] The phosphor layer in the obtained wavelength conversion sheet was visually observed and evaluated for the presence or absence of uneven light emission.

[0195] [Table 3]

[0196]

[0197] Explanation of symbols

[0198] 10···Barrier film; 11···Barrier film substrate; 12···Inorganic thin film layer; 13···Gas barrier coating layer; 20···Adhesive layer; 30···Support film; 40···Functional layer; 50···Laminated film; 55···Main body; 60···Adhesive layer; 70···Peeling film; 80···Primer layer; 100, 110, 120···Phosphor protective film; 200···Phosphor layer; 201···Phosphor; 202···Sealing resin; 310···Light guide plate; 320···Reflecting plate; 330···Light source; 500, 600···Wavelength conversion sheet with release film; 700, 800···Wavelength conversion sheet; 900···Light-emitting unit.

Claims

1. A method for manufacturing a wavelength conversion sheet, comprising: A step of laminating a laminated film having a barrier film and a release film that can be peeled off from the laminated film to obtain a phosphor protection film, wherein the barrier film has a barrier film substrate; A phosphor layer forming step of forming a phosphor layer containing a phosphor on the surface of the phosphor protection film on the laminate film side to obtain a wavelength conversion sheet with a release film; and a peeling step of peeling the peeling film from the wavelength conversion sheet with the peeling film attached thereto, The laminate film includes a support film disposed between the barrier film and the release film.

2. The manufacturing method according to claim 1, wherein: In the laminating step, the laminated film and the release film are laminated with wrinkles of the laminated film smoothed out.

3. The manufacturing method according to claim 1 or 2, wherein: In the phosphor layer forming step, the phosphor layer is formed between two phosphor protection films.

4. The manufacturing method according to any one of claims 1 to 3, wherein: The total thickness of the support film and the release film accounts for 60% or more of the total thickness of the phosphor protection film.

5. The manufacturing method according to any one of claims 1 to 3, wherein: The laminated film has no support film between the barrier film and the release film, The thickness of the release film accounts for more than 50% of the total thickness of the phosphor protection film.

6. The manufacturing method according to any one of claims 1 to 5, wherein: The barrier film substrate has a thickness of 9 μm to 25 μm.

7. The manufacturing method according to any one of claims 1 to 6, wherein: The barrier film includes a barrier film substrate and an inorganic thin film layer provided on the barrier film substrate.

8. The manufacturing method according to any one of claims 1 to 7, wherein: The laminate film has a functional layer on the surface of the release film side. The functional layer is a layer that exerts at least one function selected from the group consisting of an interference fringe prevention function, an antireflection function, a light scattering function, an antistatic function, and a damage prevention function.

9. The manufacturing method according to claim 8, wherein: The deviation (3σ) of the total thickness of the laminated film is 1.5 μm or more, and the dynamic friction coefficient of the surface of the functional layer is 0.4 or less.

10. The manufacturing method according to any one of claims 1 to 9, wherein: The deviation (3σ) of the total thickness of the phosphor protection film is 1.0 μm or less.

11. The manufacturing method according to any one of claims 1 to 9, wherein: The peel strength between the laminated film and the release film based on JIS K6854-3 is 0.05 N / 25 mm to 1.0 N / 25 mm.

12. A fluorescent substance protective film, comprising: a laminated film having a barrier film and a functional layer, and a peeling film provided on one surface of the laminated film and capable of being peeled off from the laminated film, wherein the barrier film has a barrier film substrate, The deviation (3σ) of the total thickness of the phosphor protection film is less than 1.0 μm, The laminated film and the release film are bonded together via an adhesive layer. The barrier film has a structure in which an inorganic thin film layer and a gas barrier coating layer are sequentially stacked on a barrier film substrate.

13. The phosphor protection film according to claim 12, wherein: The laminate film includes a support film disposed between the barrier film and the release film. The total thickness of the support film and the release film accounts for 60% or more of the total thickness of the phosphor protection film.

14. The phosphor protection film according to claim 12, wherein: The laminated film has no support film between the barrier film and the release film, The thickness of the release film accounts for more than 50% of the total thickness of the phosphor protection film.

15. The phosphor protection film according to any one of claims 12 to 14, wherein: The barrier film substrate has a thickness of 9 μm to 25 μm.

16. The phosphor protection film according to any one of claims 12 to 14, wherein: The barrier film includes a barrier film substrate and an inorganic thin film layer provided on the barrier film substrate.

17. The phosphor protection film according to any one of claims 12 to 16, wherein: The laminate film has a functional layer on the surface of the release film side. The functional layer is a layer that exerts at least one function selected from the group consisting of an interference fringe prevention function, an antireflection function, a light scattering function, an antistatic function, and a damage prevention function.

18. The phosphor protection film according to claim 17, wherein: The deviation (3σ) of the total thickness of the laminated film is 1.5 μm or more, and the dynamic friction coefficient of the surface of the functional layer is 0.4 or less.

19. The phosphor protection film according to any one of claims 12 to 18, wherein: The deviation (3σ) of the total thickness of the phosphor protection film is 1.0 μm or less.

20. The phosphor protection film according to any one of claims 12 to 19, wherein The peel strength between the laminated film and the release film based on JIS K6854-3 is 0.05 N / 25 mm to 1.0 N / 25 mm.

21. A wavelength conversion sheet with a release film, comprising two fluorescent material protective films according to any one of claims 12 to 20, wherein a fluorescent material layer containing a fluorescent material is sandwiched between the two fluorescent material protective films, The two fluorescent substance protection films are arranged so that the release film becomes the outermost layer. 22 . A wavelength conversion sheet obtained by peeling the release film from the wavelength conversion sheet with a release film according to claim 21 .

Citation Information

Patent Citations

  • Color conversion member and display device

    JP2011013567A

  • Laminated article and method for manufacturing light-emitting device using same

    CN105637660A

  • Functional film and method for producing functional film

    CN107405873A

  • Gas barrier film, method for transferring gas barrier film, wavelength conversion film, retardation film with gas barrier layer, and organic EL laminate

    CN107848254A

  • Gas barrier film and color conversion member

    WO2018079495A1